"Counsels of Wisdom: An ancient Babylonian instruction for scribal students" - Lenzi, Alan (Religion compass, 2021)
This article provides a historical and cultural contextualization of the Babylonian poem entitled "Counsels of Wisdom," an example of the ancient "instruction" genre also attested in Egyptian and Biblical literature. After a brief description of the poem's textual basis and reconstruction from cuneiform tablets, the article offers an interpretation of the poem within the context of Babylonian scribal curricula. Specifically, the article argues "Counsels of Wisdom" was a pedagogical text that school masters used to instill important personal and professional values in future scribes during their training. In the course of developing this interpretation, the article also presents an introductory literary treatment of "Counsels of Wisdom," including discussions of the poem's genre, structure, content, poetics, and ethical and religious perspectives.